Pengelolaan Taman Pendidikan Al-Qur’an (TPQ) Misbahul Huda Desa Duri Kecamatan Slahung Kabupaten Ponorogo Berbasis Ekonomi Mandiri: Pengelola, TPQ, Ekonomi - Eka, Ayu Kharisma; Mujahidin, Anwar (Jurnal Abdimas Multidisiplin, 2023)
Community Service Lecture Program through an Islamic-based community approach program and encouraging the successors of the younger generation. One of the many institutions in the field of religious education among the community is the Qur’an Education Park, an effort to approach the introduction of the Qur’an and As-Sunnah. However, although there have been many TPQs established and a large number of students and good administration, there are still TPQs that experience ups and downs in the midst of rural and upper-middle economic communities, one of which is TPQ Misbahul Huda in Duri Village, Slahung District. This TPQ is located in the middle of a village where the community may still have an ups and downs economy, but the awareness of parents to educate children who are good at the Koran is very high. The way to manage TPQ which is used as a reinforcement is an approach to community empowerment, asset based community driven development (ABCD). ) which has a paradigmatic basis and fundamental principles. The paradigms and principles that exist in TPQ are the main reference and at the same time make this approach characteristic and distinguish it from other approaches in community development and empowerment. The management carried out in TPQ Misbahul Huda Duri aims to develop and advance Islamic religious education. In addition, to increase efforts to generate financial income which will be used for the benefit of the community. In this service to develop the Qur’anic generation, in this case the mosque must be the main educational forum. The mosque-based community service program is an effort to strengthen TPQ ustad/ustadzah to be oriented towards religious knowledge, then the growth of the spirit of learning the high Koran from children and parents and then optimizing the mosque’s income which in the future can be used by the community.